EVALUATING SERVICE QUALITY, CUSTOMER SATISFACTION, AND PERCEIVED TRUST OF ISLAMIC DIGITAL BANKS: INDONESIA AND MALAYSIA - Al-Kamal, Abdullah Muhammad; Andriani Samsuri; Muhamad Abrar bin Bahaman; Imran Arshad; Nizar Hosfaikoni Hadi; Muhammad Widyarta Wijaya (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
Islamic digital banks operate entirely online, without physical offices, making the service quality of their apps a key factor in shaping customer satisfaction and trust. However, empirical evidence on how digital service quality affects satisfaction and how satisfaction plays a role in building trust remains limited, especially in Indonesia and Malaysia, where the Islamic digital banking industry is still in its early stages. This study aims to evaluate the influence of five dimensions of service quality, as defined by the SERVQUAL model, on customer satisfaction and to examine the role of satisfaction in building trust in Islamic digital banks. This study uses a quantitative approach, based on a survey of 284 users of Islamic digital banks in Indonesia and Malaysia. The data were analyzed using Structural Equation Modeling with the Partial Least Squares method. Service quality variables include tangibles, reliability, assurance, responsiveness, and empathy, with satisfaction as a mediator and trust as a dependent variable. The results show that only tangibles and assurance significantly affect customer satisfaction in both countries, while empathy and responsiveness show different effects across countries. Furthermore, satisfaction has a positive effect on trust and acts as a partial mediator in the relationship between service quality and trust. It confirms that improving the quality of digital services, particularly the ease of use of applications, assurance of Sharia compliance, and strong relationships and communication with customers, is an essential strategy for building long-term satisfaction and trust. Further research is recommended to include other variables to broaden understanding.